2020
DOI: 10.1186/s13045-020-00930-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD47 in Hematological Malignancies

Abstract: CD47, or integrin-associated protein, is a cell surface ligand expressed in low levels by nearly all cells of the body. It plays an integral role in various immune responses as well as autoimmunity, by sending a potent "don't eat me" signal to prevent phagocytosis. A growing body of evidence demonstrates that CD47 is overexpressed in various hematological malignancies and its interaction with SIRPα on the phagocytic cells prevents phagocytosis of cancer cells. Additionally, it is expressed by different cell ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 104 publications
2
89
0
1
Order By: Relevance
“…It is worth to mention that CD47 may mediate many different biologic activities besides its immunoregulatory functions. CD47 is not only a receptor for SIRP and the matricellular protein thrombospondin-1 (TSP-1), but also for ligands that are emerging [ 40 ]. Evidence has indicated that CD47 is a versatile factor in cell activity, such as in angiogenesis [ 41 , 42 ], cell migration, immune-cell filtration [ 43 ], as well as cell death [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth to mention that CD47 may mediate many different biologic activities besides its immunoregulatory functions. CD47 is not only a receptor for SIRP and the matricellular protein thrombospondin-1 (TSP-1), but also for ligands that are emerging [ 40 ]. Evidence has indicated that CD47 is a versatile factor in cell activity, such as in angiogenesis [ 41 , 42 ], cell migration, immune-cell filtration [ 43 ], as well as cell death [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the correlation between U-CLL and CD38 expression was not found in another study [48]. Higher levels of CD47 are also related to U-CLL [49]. Compared to M-CLL, U-CLL is 4 times more likely to develop Richter syndrome (RS) [38].…”
Section: Ighv Mutation Statusmentioning
confidence: 95%
“…Lately, enhanced CD47 expression was linked to CD123 expression and shown to be responsible for drug resistance in AML that could be overcome by treatment with the histone deacetylase inhibitor Romidepsin [ 126 ]. However, phase 1 trials using monoclonal anti-CD47 antibodies were terminated due to insufficient activity (CC-90002, NCT02641002) [ 127 ], life threatening side effects (Ti-061, 2016-004372-22; Hu5F9-g4, NCT02678338), or anemia (due to CD47 expression on red blood cells [ 128 ]). Results from other currently recruiting clinical trials are underway.…”
Section: Therapeutic Targeting Of Lscmentioning
confidence: 99%